Correlation of Levels of Lactic Acid and Glucose in Cerebrospinal Fluid of Cerebral Hemorrhage Patients with the Occurrence of Postoperative Intracranial Infection and Clinical Prognosis: Lactic Acid and Glucose Correlation in Hemorrhage Patients - Zhang, Lei; Zhang, Yan; Wang, Xiaotian; Zhao, Yun (Journal of Medical Biochemistry, 2023)
Background: To analyze the correlation of the levels of lactic acid and glucose in cerebrospinal fluid (CSF) of cerebral hemorrhage patients with the postoperative intracranial infection and clinical prognosis. Methods: The study selected the clinical data of 324 patients with cerebral hemorrhage who underwent surgical treatment in our hospital from March 2020 to March 2022 for retrospective analysis, and divided these patients into the intracranial infection group (Group A, n=22, leukocyte values in CSF>5×106/L) and the non-intracranial infection group (Group B, n=302, leukocyte values in CSF≤5×106/L) according to the occurrence of postoperative intracranial infection in patients to detect the levels of lactic acid and glucose in CSF at different times in the two groups. Pearson method was adopted to analyze the correlation of the levels of lactic acid and glucose in CSF of patients with intracranial infection, and the Glasgow Outcome Scale (GOS) was used to assess the clinical prognosis of patients. According to their scores, these patients were divided into two groups, namely, the good prognosis group (GPG, scores of 4-5 points, n=178) and the poor prognosis group (PPG, scores of 1-3 points, n=146). The levels of lactic acid and glucose in CSF of patients in the two groups were measured, and Pearson method was adopted to analyze the the relationship between these levels and clinical prognosis. Results: Compared with the Group B, the Group A had markedly higher lactic acid levels in CSF of patients at T1, T2 and T3 (P